Assessing volcanic origins within detrital zircon populations – A case study from the Mesozoic non-volcanic margin of southern Australia - Barham, Milo; Kirkland, Chris; Danisik, Martin (CHINA UNIV GEOSCIENCES, BEIJING, 2019)
© 2019 China University of Geosciences (Beijing) and Peking University. Detrital zircon U/Pb geochronology is a common tool used to resolve stratigraphic questions, inform basin evolution and constrain regional geological histories. In favourable circumstances, detrital zircon populations can contain a concomitant volcanic contribution that provides constraints on the age of deposition. However, for non-volcanic settings, proving isolated detrital zircon grains are from contemporaneous and potentially remote volcanism is challenging. Here we use same grain (U–Th)/He thermochronology coupled with U/Pb geochronology to identify detrital zircon grains of contemporary volcanic origin. (U–Th)/He ages from Cretaceous zircon grains in southern Australia define a single population with a weighted mean age of 104 ± 6.1 Ma, indistinguishable from zircon U/Pb geochronology and palynology (∼104.0–107.5 Ma). Detrital zircon trace-element geochemistry is consistent with a continental signature for parent rocks and coupled with detrital grain ages, supports derivation from a >2000 km distant early- to mid-Cretaceous Whitsunday Volcanic Province in eastern Australia. Thus, integration of biostratigraphy, single-grain zircon double-dating (geochronology and thermochronology) and grain geochemistry enhances fingerprinting of zircon source region and transport history. A distal volcanic source and rapid continental-scale transport to southern Australia is supported here.